211 The prevalence and characteristics of multiple sclerosis-associated uveitis in UK biobank. Issue 6 (27th May 2022) - Taylor, Thomas; Jacobs, Benjamin; Giovannoni, Gavin; Dobson, Ruth
Abstract : Background: Uveitis describes intraocular inflammation of the uveal tract. It may be associated with auto- immune diseases (e.g. ankylosing spondylitis), inflammatory diseases (e.g. Crohn's), infections (TB, toxoplas- mosis) or it may be idiopathic, however an association with Multiple Sclerosis (MS) has also been observed. Methods: 2151 individuals with MS were identified within UK Biobank via ICD-10 code G35 and self-reported diagnosis, and compared to the remainder of the Biobank cohort. Uveitis was defined using ICD-10 codes H20, H30, and H22.1 along with self-report. We used multivariate logistic regression to model uveitis diagnosis on MS status and control for confounding factors (age, sex, and socio-economic status). Results: Uveitis prevalence in people with MS was 0.60%, compared to 0.18% in controls. 3 individuals with MS and uveitis had an additional diagnosis associated with uveitis (ankylosing spondylitis and sarcoid) and were excluded, leaving a prevalence of 0.48%. The odds ratio (OR) of uveitis in MS was 2.73, 95%CI 1.46–5.10, p = 0.0068. 90% people with dual diagnosis were female. 30.0% were DRB1*15 heterozygotes, while 70.0% carried no copies of the DRB1*15 risk allele. Conclusions: These findings support the suggested association of these two conditions and demonstrate a comparable predominance of white females with both conditions. thomasrptaylor@gmail.com